(Des)construindo persona - Schwarz, Pedro Max (2016)
The purpose of this research is to make an analysis of the themes and aesthetics of the film Persona, from Ingmar Bergman, 1966. The first chapter is my analysis of the work, following the model of the writers Anne Goliot-Lété and Francis Vanoye, and the second chapter discusses the critical texts, analysis and interviews connected to the film. I also discussed the difficulties related to the interpretation of movies, and I tried in my own analysis to be very close to the movie itself, despite the tentations to invent more.